(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
Orally disintegrating drug delivery is currently the gold standard in the pharmaceutical industry where it is regarded as the fastest, safest, convenient, and most economic method of drug delivery having the highest patient compliance and preferred over conventional tablets. The goal of this study was to formulate and evaluate oral disintegrating tablets (ODTs) of Metoclopramide hydrochloride to overcome swallowing difficulties. The key to developing successful ODT formulation by direct compression method is to select the right super disintegrant. Nine formulations were prepared using different super disintegrants such as sodium starch glycolate (SSG), croscarmellose sodium (CCS), and crospovidone (CP) at three concentrations i.e. 2.8 %, 4 %, and 4.8 %. The formulation was evaluate for pre and post-compression parameters like angle of repose, compressibility index, Hausner’s ratio, uniformity of content, thickness, hardness, friability, drug content, wetting time, water absorption ratio, dispersion time, in-vitro disintegration time etc. Results revealed that among the 9 formulations, the formulation MHF9 containing 4.8 % of crospovidone was selected as the best formulation as its wetting time 28 second, disintegration and dispersion time 7 second and 18 seconds, percentage drug release after 15 minutes was 102.52 %.